Menstrual cycle and competitive bidding - Matthew Pearson; Burkhard C. Schipper (University of California, Department of Economics, 2011)
In an experiment using two-bidder first-price sealed bid auctions with symmetric independent private values and 400 participants, we collected information on the female participants' menstrual cycles and the use of hormonal contraceptives. We find that naturally cycling women bid significantly higher than men and earn significantly lower profits than men except during the midcycle when fecundity is highest. We suggest an evolutionary hypothesis according to which women are predisposed by hormones to generally behave more riskily during their fecund phase of their menstrual cycle in order to increase the probability of conception, quality of offspring, and genetic variety. We also find that women on hormonal contraceptives bid significantly higher and earn substantially lower profits than men. This may be due to progestins contained in hormonal contraceptives or a selection effect. We discuss how our study differs from Chen, Katuscak, and Ozdenoren (2009).
Keywords: C72; C91; C92; D44; D81; D87; 330; Hormones; Menstrual cycle; Gender; Fecundity; Contraceptives; Pill; First-price auction; Risk behavior; Competition; Bidding; Endocrinological economics.